Legal Concept of Corporate Income Tax Rates In The Work Agreement For The 3rd Generation Coal Mining Company To Create Legal Certainty - Jukipli, Jukipli; Ismail, Ismail; Hartana, Hartana (jurnal.unprimdn.ac.id, 2026)
This study examines the normative disharmony between the provisions of Corporate Income Tax (PPh) in the Generation III Coal Mining Work Agreement (PKP2B) and the generally applicable PPh Law. Article 14 number 3 letter i of the Generation III PKP2B sets a maximum progressive rate of 30% for Taxable Income above Rp50,000,000, but also contains a clause that allows for a lower rate through Government Regulations and adjustments to the PKP layer through a Decree of the Minister of Finance. Meanwhile, the PPh Law has reduced the Corporate Income Tax rate from 25% to 22% through the Law on Harmonization of Tax Regulations (UU HPP). The difference in interpretation gives rise to two conflicting principles: